PENGARUH LAMA WAKTU PENGOMPOSAN TERHADAP KANDUNGAN HARA PUPUK ORGANIK KoHeA+MF - Sondang, Yun; Fitri, Febria; Wulantika, Trisia; Sembiring, Ngakumalem; Hardaningsih, Wiwik; Wahono, Sentot; Khazyanty, Khazyanty (Fakultas Pertanian, Universitas Janabadra, 2024)
The quality of organic fertilizer produced from the composting process depends on the basic ingredients used and the length of time for composting. The quality of organic fertilizer that meets the standards will affect soil fertility and plant growth. The aim of this research was to see the effect of the length of composting time on the nutrient content of KoHeA+MF organic fertilizer.. The length of composting time is 7, 14 and 21 days. The parameters observed included pH, C-organic, N-total, P2O5, K2O, Mg-total, Ca-total and CEC. The results obtained at 21 days the content of C-organic, N-total, P2O5 and CEC was higher compared to 7 and 14 days. In general, the length of composting time does not really affect the nutrient content of the KoHeA+MF organic fertilizer produced. At 7 days composting time has met the quality standards of organic fertilizers that can be used to improve soil fertility and increase crop production.